Mitigating student resistance: the role of chatbots in sustainable educational technology integration - Al Mulhim, Ensaf Nasser (Frontiers in Education, 2025)
The sustainable integration of artificial intelligence (AI) in education is crucial for achieving Sustainable Development Goal 4 (SDG 4). However, its potential is frequently undermined by a critical, often overlooked barrier: student resistance to technological change, which can hinder learning outcomes and derail the sustainable adoption of digital tools. This study investigates the potential of chatbots as a targeted intervention to mitigate this resistance among high school students. The research involved 52 first-year high school students from a school in Al-Ahsa, selected based on high levels of technology resistance. Using a randomized controlled pre-test/post-test design, participants were divided into an experimental group (n = 26), which interacted with a dedicated chatbot, and a control group (n = 26), which was exposed to traditional teaching methods about the technology. Conducted over two weeks during the 2024/2025 academic year, resistance was measured using a validated 17-item scale assessing four dimensions: routine adherence, emotional reactions, cognitive rigidity, and short-term thinking. Data were analyzed using independent samples t-tests. The analysis revealed a statistically significant reduction in overall technology resistance for the experimental group compared to the control group (t(50) = 11.21, p < 0.001), with a large effect size (d = 2.87). The findings offer clear practical implications. For schools, chatbots represent a scalable strategy to ease digital transformation; for teachers, they are a tool to reduce student anxiety and ease instructional transitions; and for students, they provide a low-stakes environment to build technological confidence. This study provides one of the first empirical evidence that chatbots can be a targeted intervention for reducing student resistance, thereby offering a practical mechanism for supporting the sustainable and frictionless integration of new technologies in line with national visions like Saudi Vision 2030.